2017
DOI: 10.1002/14651858.cd002025.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine for managing opioid withdrawal

Abstract: Background Managed withdrawal is a necessary step prior to drug-free treatment or as the endpoint of substitution treatment. Objectives To assess the effects of buprenorphine versus tapered doses of methadone, alpha 2-adrenergic agonists, symptomatic medications or placebo, or different buprenorphine regimens for managing opioid withdrawal, in terms of the intensity of the withdrawal syndrome experienced, duration and completion of treatment, and adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 124 publications
0
70
1
Order By: Relevance
“…[69][70][71] If withdrawal management is offered as part of an immediate transition to psychosocial or residential treatment, then, among available pharmacologic approaches used for withdrawal management, a buprenorphine-naloxone taper may offer advantages such as faster symptom relief and higher rates of withdrawal completion over methadone tapers. 71 If cessation of opioid use is achieved, oral naltrexone can be considered as an adjunct medication to support abstinence (low-quality evidence).…”
Section: Offering Withdrawal Management Alone (Ie Detoxification Wmentioning
confidence: 99%
“…[69][70][71] If withdrawal management is offered as part of an immediate transition to psychosocial or residential treatment, then, among available pharmacologic approaches used for withdrawal management, a buprenorphine-naloxone taper may offer advantages such as faster symptom relief and higher rates of withdrawal completion over methadone tapers. 71 If cessation of opioid use is achieved, oral naltrexone can be considered as an adjunct medication to support abstinence (low-quality evidence).…”
Section: Offering Withdrawal Management Alone (Ie Detoxification Wmentioning
confidence: 99%
“…4 In adults, sublingual buprenorphine is used to reduce symptoms of opioid withdrawal. 6 Buprenorphine has a wide therapeutic index for respiratory depression and a long half-life that may make it useful for treatment of the neonatal abstinence syndrome. Open-label investigations have established a pharmacokinetic profile in neonates 7 and suggested favorable safety and efficacy for this indication.…”
mentioning
confidence: 99%
“…Since the 1990s, there have been dozens of RCTs and several systematic reviews that examine the effectiveness of buprenorphine versus other pharmacological treatments, including methadone. The most recent Cochrane systematic review examined 27 RCTs and concluded that buprenorphine is about as effective as methadone in ameliorating withdrawal and suggested no difference in average treatment duration (Gowing et al, 2017). Compared with other pharmacological treatments, such as clonidine and lofexidine, buprenorphine was found to be superior in treatment retention and reducing withdrawal severity.…”
Section: Box 11 Fda-approved Medications Currently Offered For Treamentioning
confidence: 99%